2001
DOI: 10.1159/000046002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialysis Dose on Nutritional Status of Children on Chronic Hemodialysis

Abstract: It had been suggested that larger hemodialysis (HD) doses in children could result in better appetite, higher protein intake, better nutritional status and better growth. We investigated how different HD doses affect protein intake and nutritional status of children on chronic HD. Indices of nutritional status used were normalized protein catabolic rate (nPCR) calculated by formal 3-sample urea kinetic modeling and serum albumin level. Data of 38 HD sessions in 15 stable patients (6 males, 9 females) aged 14.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…Patient nutritional status was not related to the delivered dose of dialysis over the time course of study, since patients in both the pre-IDPN and IDPN periods received a mean spKt/V>1.4. We do not suggest that spKt/V>1.4 is an optimal or even adequate dose of dialysis, although one pediatric study reported improvement in nPCR and appetite in patients with spKt/V>1.3 compared with patients with spKt/V<1.3 [25]. Nevertheless, the current study demonstrates that hemodialysis patient outcome is dependent on more than just the amount of urea clearance during hemodialysis; delivery of optimal hemodialysis also requires assessment of nutritional status.…”
Section: Discussioncontrasting
confidence: 56%
“…Patient nutritional status was not related to the delivered dose of dialysis over the time course of study, since patients in both the pre-IDPN and IDPN periods received a mean spKt/V>1.4. We do not suggest that spKt/V>1.4 is an optimal or even adequate dose of dialysis, although one pediatric study reported improvement in nPCR and appetite in patients with spKt/V>1.3 compared with patients with spKt/V<1.3 [25]. Nevertheless, the current study demonstrates that hemodialysis patient outcome is dependent on more than just the amount of urea clearance during hemodialysis; delivery of optimal hemodialysis also requires assessment of nutritional status.…”
Section: Discussioncontrasting
confidence: 56%
“…This study showed no significant correlation between height z-score and Kt/V. This is in accordance with studies stated that although adequate dialysis needs to be achieved in order to ensure good protein intake, high dialysis doses (< 1.6) are of no further benefit [30]. This, however, doesn't exclude the possibility that a Kt/V less than 1.2 would be associated with poor growth.…”
Section: Discussionsupporting
confidence: 88%
“…We do not have individual data on all our patients, another deficiency of our study, but our aim is for a Kt/V of >1.6 per session for HD and >2.1 per week for PD. One study in children has shown improvement in growth with a better Kt/V [6,21], but there appears to be a ceiling above which no further benefit is seen [22].…”
Section: Discussionmentioning
confidence: 99%